Association between family nurturing environment and screen exposure among preschool children aged 3–6 years in Shanghai: A cross-sectional study - Min Chen; Yun Li; Shurong Kang; Chunhua Jiang; Yinan Liu; Jian Li (PLoS ONE, 2026)
Background Excessive or early screen exposure has been deemed associated with both immediate and long-term health impairment among preschool children. This study aimed to investigate the association between family nurturing environment and screen exposure among preschool children aged 3–6 years. Materials and methods A multi-stage stratified cluster sampling method was utilized to sample the kindergarten children aged 3-6 years from a district in Shanghai, China. From April to May 2023, parents completed an online questionnaire. Children's screen exposure was defined as more than 1 hour (hr) per day of screen-based devices use, and the daily screen time was categorized into three groups: non-exposure (<1hr/ day), low exposure (1-4 hrs/ day), and high exposure (>4 hrs/ day). Univariate and multivariate cumulative logit regression models were adopted to identify the determinants of screen exposure. Results A total of 1917 preschool children were included. Of these, 1604 (83.7%) were exposed to screens for more than 1 hr per day. High, low, and non-exposure groups comprised 313 (16.3%), 1291 (67.4%), and 313 (16.3%) children, respectively. The multivariate cumulative logit model showed that parental education, monthly household income, presence of screen-based devices in the bedroom, and parental screen use in front of children were positive determinants of more severe screen exposure for preschoolers. Conversely, older age, absence of siblings, co-viewing with the child, and parental restriction of screen time were negative determinants of more severe screen exposure. Conclusions Our findings suggest that interventions targeting parental behavior and cognitive practices may be more effective in promoting healthy screen exposure habits in preschool children.